2017
DOI: 10.1073/pnas.1711235114
|View full text |Cite|
|
Sign up to set email alerts
|

Gut bacteria from multiple sclerosis patients modulate human T cells and exacerbate symptoms in mouse models

Abstract: SignificanceWe have experimentally investigated the immunoregulatory effects of human gut microbiota in multiple sclerosis (MS). We have identified specific bacteria that are associated with MS and demonstrated that these bacteria regulate T lymphocyte-mediated adaptive immune responses and contribute to the proinflammatory environment in vitro and in vivo. Thus, our results expand the knowledge of the microbial regulation of immunity and may provide a basis for the development of microbiome-based therapeutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
742
3
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(835 citation statements)
references
References 38 publications
32
742
3
9
Order By: Relevance
“…A critical contribution of the microbiota to autoimmune diseases was recently underpinned by the observation that transfer of MS patients microbiota into mice could modulate EAE. GF mice reconstituted with MS patient microbiota developed more severe EAE attributed to a diminished generation of IL‐10 producing Tregs compared with GF mice reconstituted with microbiota derived from healthy controls . A finding shared by another study using GF relapsing–remitting (RR) mice as recipients of MS patient microbiota.…”
Section: Introductionmentioning
confidence: 93%
“…A critical contribution of the microbiota to autoimmune diseases was recently underpinned by the observation that transfer of MS patients microbiota into mice could modulate EAE. GF mice reconstituted with MS patient microbiota developed more severe EAE attributed to a diminished generation of IL‐10 producing Tregs compared with GF mice reconstituted with microbiota derived from healthy controls . A finding shared by another study using GF relapsing–remitting (RR) mice as recipients of MS patient microbiota.…”
Section: Introductionmentioning
confidence: 93%
“…The results obtained in the studies of transplantation of fecal content of patients with MS to germ-free mice that suffer from a less severe form of EAE suggest that changes in the microbiota of individuals with MS could be functionally relevant by enhancing experimental disease. Pröbstel and Baranzini [20] review their own [22] and findings by Berer et al [23], providing evidence for the importance of alterations of the microbiota in the severity and progression of the disease. Fecal transplantations of MS samples were able to restore EAE susceptibility in 2 different models of germ-free mice.…”
mentioning
confidence: 99%
“…Are these changes relevant? Two recent studies evaluated whether the changes in the specific taxa observed in patients with MS had functional effects on disease [22,23]. The results obtained in the studies of transplantation of fecal content of patients with MS to germ-free mice that suffer from a less severe form of EAE suggest that changes in the microbiota of individuals with MS could be functionally relevant by enhancing experimental disease.…”
mentioning
confidence: 99%
“…The mode of health-promoting mechanisms include the increase of mucus thickness and gut barrier function (Everard et al 2013), direct host immune stimulation (Ottman et al 2017b), and stimulation of a beneficial mucosal community (Chapter 4 and 5) . Nevertheless, the relative abundance of Akkermansia muciniphila has also been associated with negative health consequences such as Parkinson's disease (Heintz-Buschart et al 2018), Alzheimer's disease (Vogt et al 2017), multiple sclerosis (Cekanaviciute et al 2017) and colorectal cancer . These health associations are mainly demonstrated in mouse models, and often the design of the above-mentioned studies are not as robust as those that demonstrate beneficial effect.…”
Section: Novel Probiotic Strainsmentioning
confidence: 99%